A CONCEPT OF AUGMENTED REALITY MODULE FOR ELECTRONIC SUBJECT - Johar, Siti Hajar; Abdullah, Nurhanim Saadah (Online Journal for TVET Practitioners, 2018)
Augmented reality is a popular technology used extensively in various fields and is also used in education. At the present time in the process of teaching and learning, there are a number of changes in terms of infrastructure and instructional materials. Today, the use of Augmented Reality applications is widely practiced in education because it does not require sophisticated and expensive hardware. However, its effectiveness is still not clearly visible, especially for Electrical and Electronics subjects. Hence, the aim of this study is to develop the Electronic module using the Augmented Reality application as one of the teaching aid tools. The expectations of the study is the Electronic module to be developed will attract students, especially those who enroll Electronic Subject. The study is also expected to be help student in understanding the basic concept of electronic topics such as semiconductors, transistors and diodes. At the same time it is expected to be able to assist students pursuing a Bachelor's Degree in Vocational Education (Electrical and Electronics) in particular to understand more deeply about the difficult topics in Electronic subject and to make improvements to optimize the effectiveness of the Electronic module using the Augmented Reality application.